Development of An Android-Based Virtual Laboratory Using The Adobe Animate Application For Urine Tests at SMA Negeri 3 Mataram - Kurniati, Sri; Hadiprayitno, Gito; Lestari, Tri Ayu (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
: This research aims to determine the validity of Android-based virtual laboratory products with the Adobe Animate application. Practicality of Android-based virtual laboratory products with the Adobe Animate application. Student responses to Android-based virtual laboratory products developed with the Adobe Animate application. The research methods used are R&D with the ADDIE Analyze model (identifying problems and finding solutions to the problems found), Design (designing the components needed to develop products and other instruments used at the implementation stage), Development (product development) , Implementation (implemented in the learning process involving students), and Evaluation (measuring the quality of products that have been developed and processed before and after learning using a virtual laboratory). The research results show that the Android-based virtual laboratory product developed has an average readability score of 89.98% with very good criteria. The Android-based virtual laboratory media developed has met the very valid criteria with an average score of 95%. The practicality of the laboratory being developed has met the very practical criteria with an average score of 82.5% and students' responses to Android-based virtual laboratory products include the criteria of agreeing with an average percentage score of 83.33%.